Pengaruh Good Corporate Governance dan Penerapan Green Accounting terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia) - Sitti Nurcahyani; Samirah Dunakhir; Nur Afiah (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2026)
This study aims to analyze the effect of Good Corporate Governance, proxied by managerial ownership and institutional ownership, as well as Green Accounting on firm value in mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The study employs secondary data collected through documentation and uses purposive sampling, resulting in a sample of 9 companies. Panel data regression analysis with the Fixed Effect Model (FEM) was applied using EViews. The regression results show that managerial ownership has a positive but insignificant effect on firm value, institutional ownership has a negative and significant effect on firm value, and Green Accounting has a positive but insignificant effect on firm value. However, simultaneously, managerial ownership, institutional ownership, and Green Accounting have a significant effect on firm value. These findings indicate that the implementation of Good Corporate Governance and Green Accounting practices collectively contributes to explaining variations in firm value, although not all variables show a significant individual effect.